Social class and (un)ethical behavior: Causal versus correlational evidence - Elisabeth Gsottbauer; Daniel Müller; Samuel Müller; Stefan T. Trautmann; Galina Zudenkova (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
Are upper class individuals less ethical? Highly popularized research findings support this notion. This paper provides a novel test to evaluate the relationship between social status and ethical behavior. We successfully prime a large heterogeneous sample of the German population as either high or low social status. We then elicit ethical behavior in an incentivized experimental task. Thus, our data allows us to study both correlation (using demographic data) and causality (using the priming). Our study does not support the claim that higher social status individuals are less ethical, as prominently suggested by the literature. This result holds both for a respondent's true social status and for her primed subjective social status. Our findings call for a re-interpretation of the existing evidence.
Keywords: D63; D31; 330; cheating; ethics; mind game; priming; social class